HMG-Like DSP1 Mediates Immune Responses of the Western Flower Thrips (Frankliniella occidentalis) Against Beauveria bassiana, a Fungal Pathogen - Ahmed, Shabbir; Roy, Miltan Chandra; Choi, Duyeol; Kim, Yonggyun (Frontiers in Immunology, 2022)
Western flower thrips, Frankliella occidentalis, is a serious pest by directly infesting host crops. It can also give indirect damage to host crops by transmitting a plant virus called tomato spotted wilt virus. A fungal pathogen, Beauveria bassiana, can infect thrips. It has been used as a biopesticide. However, little is known on the defense of thrips against this fungal pathogen. This study assessed the defense of thrips against the fungal infection with respect to immunity by analyzing immune-associated genes of F. occidentalis in both larvae and adults. Immunity-associated genes of western flower thrips were selected from three immunity steps: nonself recognition, mediation, and immune responses. For the pathogen recognition step, dorsal switch protein 1 (DSP1) was chosen. For the immune mediation step, phospholipase A2 (PLA2) and prostaglandin E2 synthase were also selected. For the step of immune responses, two phenoloxidases (PO) genes and four proPO-activating peptidase genes involved in melanization against pathogens were chosen. Dual oxidase gene involved in the production of reactive oxygen species and four antimicrobial peptide genes for executing humoral immune responses were selected. All immunity-associated genes were inducible to the fungal infection. Their expression levels were induced higher in adults than in larvae by the fungal infections. However, inhibitor treatments specific to DSP1 or PLA2 significantly suppressed the inducible expression of these immune-associated genes, leading to significant enhancement of fungal pathogenicity. These results suggest that immunity is essential for thrips to defend against B. bassiana, in which DSP1 and eicosanoids play a crucial role in eliciting immune responses.